Transformative pastoral leadership in the Black church - Tribble, Jeffery L (New York, N.Y. : Palgrave Macmillan, 2005)
"Transformative Pastoral Leadership in the Black Church offers practical wisdom from a comparative analysis of the experiences of a male pastor and a female pastor in the Christian Methodist Episcopal Church. Church leaders must be transformed themselves as they are transforming their churches to serve their communities. From his research of the perspectives of laity, clergy, and scholars of the black church, Jeffery L. Tribble, Sr., offers hopeful stories and helpful strategies for those who believe that the black church must continue its historic mission of being an instrument of survival, elevation, and liberation for its people. Transformative Pastoral Leadership in the Black Church is an important contribution to studies of black religion, womanist thought, and social justice."--BOOK JACKET
The quest for transformative pastoral leadership in the black church -- 2. "God did it" : a tale of a male pastor in a transforming traditional church -- 3. "God of a second chance" : a tale of a female pastor in a transforming merged mission church -- 4. Emerging strategies of transformative pastoral leadership in the black church -- 5. Independent black Methodist systems as contexts of transformative pastoral leadership -- App. A. Research method -- App. B. Clergy interviews -- App. C. Lay leader interviews -- App. D. Community census data
Includes bibliographical references and index